Digital Literacy:The Freedom of Speech to FaceSociety 5.0 - Levandra Balti; Winda Trisnawati (Universitas Muhammadiyah Muara Bungo, 2021)
Digital literacy, which is also known as computer literacy is one component in media literacy skills which is a proficiency in the use of computers, the Internet, telephones, and other digital devices.The development of digital technology is one aspect that effect the future life. It is known as society 5.0. Society 5.0 is a concept of a human-centered and technology-based Society. By Society 5.0, artificial intelligence (AI) will transform Big Data collected through the Internet of Things (IoT) into new wisdom. Society 5.0 also give knowledge for human in communication aspect.it is the understanding of networks performance and communications in digital world.